2021
DOI: 10.1093/nar/gkab269
|View full text |Cite
|
Sign up to set email alerts
|

HPF1-dependent PARP activation promotes LIG3-XRCC1-mediated backup pathway of Okazaki fragment ligation

Abstract: DNA ligase 1 (LIG1) is known as the major DNA ligase responsible for Okazaki fragment joining. Recent studies have implicated LIG3 complexed with XRCC1 as an alternative player in Okazaki fragment joining in cases where LIG1 is not functional, although the underlying mechanisms are largely unknown. Here, using a cell-free system derived from Xenopus egg extracts, we demonstrated the essential role of PARP1-HPF1 in LIG3-dependent Okazaki fragment joining. We found that Okazaki fragments were eventually ligated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…In accordance with the reduced PAR (Figure 6C), we observed that 53BP1 deletion in the BRCA1 KO cells reduced PARP1 chromatin association (Figures 7A and 7B). Notably, XRCC1, LIG3 (Figures 7B and 7C), and replication were instead elevated (Figure 7D), suggesting that backup OFP was in place (Arakawa and Iliakis, 2015;Hanzlikova and Caldecott, 2019;Kumamoto et al, 2021). Similarly, 53BP1 depletion suppressed PAR and elevated XRCC1 and LIG3 in BRCA1-deficient BR5 cells, indicating that restored alternative OFP was not specific to the RPE1 cells (Figures S7B and S7C).…”
Section: Bp1 Deletion Restores Lagging Strand Synthesis In Brca1 Ko C...mentioning
confidence: 95%
“…In accordance with the reduced PAR (Figure 6C), we observed that 53BP1 deletion in the BRCA1 KO cells reduced PARP1 chromatin association (Figures 7A and 7B). Notably, XRCC1, LIG3 (Figures 7B and 7C), and replication were instead elevated (Figure 7D), suggesting that backup OFP was in place (Arakawa and Iliakis, 2015;Hanzlikova and Caldecott, 2019;Kumamoto et al, 2021). Similarly, 53BP1 depletion suppressed PAR and elevated XRCC1 and LIG3 in BRCA1-deficient BR5 cells, indicating that restored alternative OFP was not specific to the RPE1 cells (Figures S7B and S7C).…”
Section: Bp1 Deletion Restores Lagging Strand Synthesis In Brca1 Ko C...mentioning
confidence: 95%
“…PARP1-dependent signalling and repair may thus help ensuring the integrity of nascent DNA strands during normal DNA replication. Consistent with this idea, SSB repair proteins recruited at DNA breaks by PARP1 such as X-ray repair cross-complementing protein 1 (XRCC1) and DNA ligase III (LIG3) have been associated with Okazaki fragment maturation 13,[29][30][31] .…”
Section: Introductionmentioning
confidence: 79%
“…However, our current and previous observations that the level of PARP1 activity is highest in S phase and is increased further if canonical Okazaki fragment processing is perturbed by FEN1 inhibition, FEN1 deletion, or LIG1 mutation is consistent with the former, as is the observation that SSB repair proteins such as XRCC1 are recruited to sites of PARP1 activity in S phase 13,[39][40][41] . Indeed, it has been reported that the XRCC1 partner protein LIG3 can replace LIG1 during Okazaki fragment processing in DT40 cells, and in Xenopus extracts 29,30,42 . However, irrespective of whether PARP1 is an active participant or bystander during Okazaki fragment processing, our data identify these and possibly other nascent strand intermediates as major sources of genome breakage and cytotoxicity in cells following treatment with PARP inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HPF1 was recently also implicated in regulation of replication. HPF1-directed PARP1 activity was shown to be required for recruitment of XRCC1/DNA ligase 3 complexes, which provide a back-up mechanism for Okazaki fragment ligation, and thus promoting repair of replication-associated DNA damage ( Kumamoto et al, 2021 ). HPF1 also cooperates with the methyltransferase CARM1 to stimulate PARP1 activity and thereby promotes slowing down of replication fork progression ( Genois et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%